2019
DOI: 10.1186/s12884-019-2683-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distraction techniques on pain and stress during labor: a randomized controlled clinical trial

Abstract: BackgroundPain control and the stress associated with labor and delivery are among the most important issues of health care system. Use of distraction techniques during childbirth is reported to reduce pain and stress of labor. However, there is a limited publication that looked on the effect of distraction techniques on labor pain and stress. Thus, the aim of this study was to determine the effect of distraction techniques on labor pain and stress (primary outcomes), fear of childbirth, length of delivery sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
2
21
0
3
Order By: Relevance
“…It was observed that women in the experimental group were able to cope with labor pain more effectively. Studies have shown that interventions by healthcare professionals that provide physical and emotional comfort (holding the woman's hand, massage, changing position, allowing taking a warm shower, ensuring hygiene, saying words of appreciation, encouraging, making eye contact, appreciating, helping focus on positive things, providing spiritual care, breathing and relaxation techniques, and distraction) are effective in the management of labor pain (Amiri et al, 2019;Bohren et al, 2016;Steel et al, 2015 ). Our study results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that women in the experimental group were able to cope with labor pain more effectively. Studies have shown that interventions by healthcare professionals that provide physical and emotional comfort (holding the woman's hand, massage, changing position, allowing taking a warm shower, ensuring hygiene, saying words of appreciation, encouraging, making eye contact, appreciating, helping focus on positive things, providing spiritual care, breathing and relaxation techniques, and distraction) are effective in the management of labor pain (Amiri et al, 2019;Bohren et al, 2016;Steel et al, 2015 ). Our study results are consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…The eight studies were published between 2006 and 2019. The studies were from the United Kingdom [30], Sweden [31], Taiwan [32], Iran [33,34], Canada [35], France [36], and Turkey [37]. All the studies evaluated participants immediately after the interventions.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…All the studies evaluated participants immediately after the interventions. There were six RCTs [30][31][32][33][34][35] and two quasi-experimental studies [36,37].…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Pregnancy and delivery are physiological events in a woman's life that, due to changes in physical conditions, family and workplace roles, and sometimes feelings and attitudes toward motherhood; require bio-psychosocial adjustment by the pregnant woman and her family [1]. This can be due to anxiety and fear of labor pain, lack of trust in the delivery room staff and stress caused by entering the unknown space of the delivery room, which is itself a factor that increases catecholamine, cortisol and epinephrine [2]. These stresses affect the adrenal axes, pituitary-hypothalamus and sympathetic nervous system, leading to endocrine neuronal changes and as a result to cortisol and adrenocorticotropin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased cortisol levels rapidly results in problematic fetal growth , developmental disorders and reduces fetal heart rate [3] . Decreased Apgar score, lactation problems, low birth weight, late attachment between mother and baby, and increased cesarean section rate are other problems associated with increased stress and anxiety levels in the mother [1,2,5].…”
Section: Introductionmentioning
confidence: 99%